Diﬀraction Radiation Generation by the Internal Target of the Cyclic Accelerator; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Uglov S. R. Sergey Romanovich (Diﬀraction Radiation and Smith-Purcell Radiation, 2019)
Title screen